Analisis Penyebab Temuan Berulang APBDES pada Audit Internal Inspektorat Daerah - Silalahi, Roubert Arsa Paringotan; Nuswantara, Dian Anita (IAI Nasional Laa Roiba Bogor, 2024)
Research indicates that recurring findings are still frequently encountered. Agency theory explains why this is the case. This study attempts to take a different angle by integrating the agency theory framework with the perspective of organizational error, identifying recurring findings as a phenomenon experienced by both auditors and auditees. The aim of this research is to analyze the causes of recurring findings in the management of village government APBDes funds during the Regular Internal Audit conducted by the Regional Inspectorate. This research is a phenomenological study using a qualitative and exploratory approach. This method is used to obtain more complete, in-depth, credible, and meaningful data by delving deeper into the research focus based on the phenomena experienced and information collected from sources through in-depth interviews, ensuring that the research objectives can be achieved. This data is triangulated with other data obtained from observation and documentation studies, then analyzed interactively by transcribing, coding, presenting in text and table formats, and drawing conclusions and interpretations. The results of this study indicate that the causes of recurring findings in the management of village government APBDes funds during the Regular Internal Audit conducted by the Regional Inspectorate from the auditor's perspective are: 1) Limited quantity of human resources available to the auditors. From the auditee's perspective, the causes are: 1) Lack of quality human resources within the village government apparatus; 2) Lack of integrity and ethical values among officials; 3) Weak internal control systems; 4) Regulations; 5) Facilities and infrastructure.